A triple-hurdle model of small-ruminant production and marketing in the highlands of Ethiopia: Implications for commercial transformation - Gebremedhin, Berhanu; Shiferaw, K.; Tegegne, Azage; Hoekstra, Dirk (2017)
This paper analyses factors that influence Ethiopian households’ decisions to produce and market small ruminants using a triple-hurdle econometric model. The model integrates production, market position and volume of sales, allowing us to make inferences relating to the study population. The results are based on a dataset collected from 5 000 households and 497 rural communities in the highlands of Ethiopia. Our results show that, among other things, younger household heads, maleheaded households, and households with relatively higher labour supply are more likely to engage in small-ruminant production. Flock size is an important determining factor of market participation and volume of sales. In addition, in areas where small-ruminant production is likely, market access stands out as an important determinant of household market position. Finally, our results show that the small-ruminant sub-sector is price nonresponsive, suggesting that households liquidate their animals in need of cash, not necessarily to maximise profit.